Lymphatic‐to‐blood vessel transition in adult microvascular networks: A discovery made possible by a top‐down approach to biomimetic model development. (8th November 2019) - Azimi, Mohammad S.; Motherwell, Jessica M.; Hodges, Nicholas A.; Rittenhouse, Garret R.; Majbour, Dima; Porvasnik, Stacey L.; Schmidt, Christine E.; Murfee, Walter L.
Abstract: Objective: Emerging areas of vascular biology focus on lymphatic/blood vessel mispatterning and the regulation of endothelial cell identity. However, a fundamental question remains unanswered: Can lymphatic vessels become blood vessels in adult tissues? Leveraging a novel tissue culture model, the objective of this study was to track lymphatic endothelial cell fate over the time course of adult microvascular network remodeling. Methods: Cultured adult Wistar rat mesenteric tissues were labeled with BSI‐lectin and time‐lapse images were captured over five days of serum‐stimulated remodeling. Additionally, rat mesenteric tissues on day 0 and day 3 and 5 post‐culture were labeled for PECAM + LYVE‐1 or PECAM + podoplanin. Results: Cultured networks were characterized by increases in blood capillary sprouting, lymphatic sprouting, and the number of lymphatic/blood vessel connections. Comparison of images from the same network regions identified incorporation of lymphatic vessels into blood vessels. Mosaic lymphatic/blood vessels contained lymphatic marker positive and negative endothelial cells. Conclusions: Our results reveal the ability for lymphatic vessels to transition into blood vessels in adult microvascular networks and discover a new paradigm for investigating lymphatic/blood endothelial cell dynamics during microvascular remodeling.